Predicaments of Polyphony: Sequence, Self and Style in Wolof Conversations - Meyer, Cristian (Africana Studia, 2020)
This chapter examines conversations that are held on the village square of a Wolof village in North-Western Senegal. These conversations are polyphonic in the sense that permanently several threads of conversation are running at one and the same time. This leads to a conversational situation where interruptions, overlaps and schisming are ubiquitous, since the participants constantly switch between the different conversational threads according to their interest. The village square conversations are thus characterized by a constant competition about the attention of the participants, which is created and maintained mainly by stylistic strategies. Thus, in this place, the participants create through their own speaking features constraining conditions that open up two alternatives: the chance to present oneself as an eloquent, likeable and attractive, hence prestigious individual and the constant risk of being disentitled of precisely this individuality through the joint production of conversations within a polyphonic interaction order. Keywords: Wolof, conversational organisation, polyphony, turn-taking, style, concept of person